Ultra-durable cell-free bioactive hydrogel with fast shape memory and on-demand drug release for cartilage regeneration - Yang, Yuxuan; Zhao, Xiaodan; Wang, Shuang; Zhang, Yanfeng; Yang, Aiming; Cheng, Yilong; Chen, Xuesi (Nature communications, 2023)
Osteoarthritis is a worldwide prevalent disease that imposes a significant socioeconomic burden on individuals and healthcare systems. Achieving cartilage regeneration in patients with osteoarthritis remains challenging clinically. In this work, we construct a multiple hydrogen-bond crosslinked hydrogel loaded with tannic acid and Kartogenin by polyaddition reaction as a cell-free scaffold for in vivo cartilage regeneration, which features ultra-durable mechanical properties and stage-dependent drug release behavior. We demonstrate that the hydrogel can withstand 28000 loading-unloading mechanical cycles and exhibits fast shape memory at body temperature (30 s) with the potential for minimally invasive surgery. We find that the hydrogel can also alleviate the inflammatory reaction and regulate oxidative stress in situ to establish a microenvironment conducive to healing. We show that the sequential release of tannic acid and Kartogenin can promote the migration of bone marrow mesenchymal stem cells into the hydrogel scaffold, followed by the induction of chondrocyte differentiation, thus leading to full-thickness cartilage regeneration in vivo. This work may provide a promising solution to address the problem of cartilage regeneration. Achieving successful in vivo cartilage regeneration remains challenging. Here they present a cell-free, multiple hydrogen-bond crosslinked hydrogel loaded with tannic acid and Kartogenin with ultra-durable mechanical properties and stage-dependent drug release behavior to promote cartilage regeneration.